UPAYA MENINGKATKAN HASIL BELAJAR ILMU PENGETAHUAN SOSIAL MELALUI PEMBELAJARAN KOOPERATIF - Amsunardi, Amsunardi (Direktorat Riset dan Pengabdian pada Masyarakat (DRPM) Universitas Bina Darma, 2019)
This study aims to improve student learning outcomes at SDN 07 Indralaya Utara Ogan Ilir Regency through cooperative learning models. This study uses a classroom action research method with the subject of research is the fifth grade students of SDN 07 Indralaya Utara, Ogan Ilir Regency. The results of this study indicate that the ability of students in subject matter fractions, each cycle has increased. Cycle I, the percentage of completeness 58.33%, students who reach the minimum completeness criteria of seven students. Cycle II with a percentage of completeness 83.33%, students who reached the minimum completeness criteria were ten students. From the two cycles applied, there was an increase in students' abilities in the subject matter of Ethnic Diversity in Indonesia. Based on indicators of success in cycle II, that applied cooperative learning can improve students abilities in the subject matter of Ethnic Diversity in Indonesia.